Factors That Influence Impulse Buying in Live Commerce in Indonesia - Akbar, Rizky; Sugiarto, Catur (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to identify factors that influence impulse buying in live commerce in Indonesia. The method used is causal explanatory research with a non-probability sampling technique using a purposive sampling approach, and data analysis was carried out using Structural Equation Modeling-Partial Least Square (SEM-PLS). The sample consisted of users of the Shopee e-commerce application who had shopped via live streaming, especially Erigo fashion products. The research results show that streamer interactivity and expertise have a positive effect on perceived enjoyment, while product usefulness and product price have an effect on perceived usefulness. Apart from that, promotional information and promotional time limits have an impact on perceived value. Other findings show that perceived enjoyment, perceived usefulness, and perceived value influence the urge to buy impulsively and act as mediating variables that strengthen the relationship between the main variables and impulsive buying. Practically, this research implies that sellers and e-commerce platform developers can optimize interactivity factors, promotional strategies, and product information to increase impulse purchases through live streaming.